Uji Larvasida Seduhan Teh Bunga Telang (Clitoria Ternatea L.) Terhadap Larva Nyamuk Aedes Aegypti Instar III - Muflihah Rizkawati; Marlina Anggraeni; Ernadita Budiastuti; Riana Rahmawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Aedes aegypti is a mosquito species capable of transmitting dengue fever to humans. Vector control aimed at disrupting the mosquito life cycle is an effective strategy for preventing dengue fever. Larvicides are a class of pesticides used to kill insects at the larval stage. Butterfly pea flowers (Clitoria ternatea L.) contain active compounds such as flavonoids, which have potential larvicidal properties. This study aimed to determine the larvicidal effect of butterfly pea flower infusion (Clitoria ternatea L.). Telang flower tea was prepared at concentrations of 10%, 5%, 2.5%, and 1.25% for the treatment groups, while abate powder was used as the positive control. The study employed a completely randomized design by placing Aedes aegypti larvae into plastic cups divided into six groups with three replications, each containing 25 larvae. The treatment groups received telang flower tea at concentrations of 10%, 5%, 2.5%, and 1.25%. Larval mortality was observed over a 24-hour period. The results demonstrated larvicidal activity, as indicated by larval mortality. The effective concentration causing 50% larval mortality was 10% after 6 hours of observation, and 5% and 10% after 12 hours. In conclusion, telang flower tea (Clitoria ternatea L.) has been proven to exhibit larvicidal activity against instar III Aedes aegypti larvae at concentrations of 10% and 5%. The phytochemical compounds present in butterfly pea flowers—namely saponins, flavonoids, and tannins exert a rapid effect on larval mortality by damaging cell membranes or disrupting larval metabolic processes.